Pemanfaatan Danau Buaya Bandar Alai Kari untuk kesejahteraan masyarakat tempatan - Rasoel Hamidy; Yusni Ikhwan Siregar; Rahmadi Rahmadi (CANANG: Jurnal Pengabdian Masyarakat, 2021)
Seeing the importance of lakes for the community and for conserving natural resources, it is necessary to act on ecosystem management by involving local communities. To provide empowerment-based education to the community, the contribution of the lake in the village of Bandar Alai Kari for the community. In overcoming existing problems, this activity is carried out through outreach with lectures, discussions, questions and answers, observation, mentoring and evaluation. The implementation of community service activities with the theme Utilizing Bandar Alai Kari Lake for the Welfare of the Local Community in  Bandar Alai Kari Village, Kuantan Tengah District, Kuantan Singingi Regency, was carried out on Wednesday, July 22, 2020. In general, the community understands  more about the importance of functions and benefits. Lake in his village and community participation in saving the lake from further damage.